PENGARUH MODEL PEMBELAJARAN GAMIFICATION TERHADAP HASIL BELAJAR IPAS SISWA KELAS V UPTD SD NEGERI 098166 PERUMNAS - Simanjuntak, Melvin; Maria Barus; Adelina Deis Frentina Purba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there is an influence of the Gamification Learning Model on the Science Learning Outcomes of Grade V Students in Learning Light and Its Properties at UPTD SD Negeri 098166 Perumnas. There are 2 hypotheses in this study, namely (1) Alternative hypothesis (Ha), there is a significant influence of the application of the Gamification Model on the Science Learning Outcomes of Grade V Students in Learning Light and Its Properties at UPTD SD Negeri 098166 Perumnas and (2) Null hypothesis (H0), there is no significant influence of the application of the Gamification Model on the Science Learning Outcomes of Grade V Students in Learning Light and Its Properties at UPTD SD Negeri 098166 Perumnas. This research is a quantitative study with a pre-experimental design using a "one group pretest-posttest design." The population of this study was all 28 fifth-grade students. Because the population size was less than 50, this population was used as the sample in this study. The data collection techniques used were tests (pretest and posttest) and documentation techniques while the data analysis used was the N-Gain Test and Hypothesis Test. Based on the results of the data analysis, it is known that the t-count result is 14.426 with a significance level of 0.05. So it can be concluded that there is an Effect of the Gamification Model on the Science Learning Outcomes of Grade V Students in Learning Light and Its Properties at the UPTD of SD Negeri 098166 Perumnas. This means that Ha is accepted and H0 is rejected.